Factors Influencing Esp Learners’ Behavioural Intention Towards The Use Of Edmodo At A Malaysian Public University - Muniandy, Jayanthi (2022)
Edmodo, a social learning network site has been acknowledged for its potential in enhancing learners’ language skills and online discussions. Nevertheless, studies on the intention to use Edmodo as a platform for a virtual learning community among ESP learners are still in dearth. The concept of a virtual learning community has emerged as an avenue to unite learners through an online learning platform although they are separated by physical distance. In the field of technology acceptance in education, studies have measured the acceptance of Edmodo through technology acceptance factors but have neglected the educational factors. Therefore, the unified theory of acceptance and use of technology (UTAUT) that consists of technology acceptance factors such as performance expectancy, effort expectancy, social influence, and facilitating condition was expanded by incorporating an educational factor, namely virtual community of practice (VCoP) to determine factors influencing ESP learners’ behavioural intention in using Edmodo as a platform for a virtual learning community. In addition, ESP learners’ individual differences such as gender, fields of study, and proficiency level were integrated as the moderating effects. The study was carried out by disseminating a questionnaire survey to 200 ESP learners and conducting focus group interviews with 16 learners